Impact of Sino-US Trade Liberalization on China’s Carbon Emissions and Future Works on Fractional Phenomenon - Yanchun Yi; Yaqing Li; Ji Qi (Discrete Dynamics in Nature and Society)
This study estimates the effects of the Sino-US trade liberalization on CO2 emissions in China and its influencing mechanism. We used the exchange of CNY/USD as the instrumental variable to alleviate the endogeneity with the two-stage least squares method. Different from the existing literature focusing on implied carbon, we use panel data of 27 provinces in China from 1998 to 2018 to examine the relationship between the Sino-US trade liberalization and CO2 emissions. We found that the Sino-US trade liberalization had a positive effect on the environment and reduced CO2 emissions.